Job Satisfaction and Organizational Commitment in Lembaga Tabung Haji Negeri Kedah - Khairul Azhan, Ghazali (2010)
The purpose of this study is to examine the relationship between components of organizational commitment and job satisfaction of Lembaga Tabung Haji Negeri Kedah. It was assumed that there has not been any similar research conducted on Tabung Haji Kedah employees.Therefore this study could make important contribution to extant research in management and organizational behaviour. Research was conducted through a survey instrument consisting of demographic, job satisfaction and organizational commitment questions adopted from the validated Minnesota Job Satisfaction and Organizational Commitment Questionnaires. The study generated a 79.2 percent response rate from 120 employees.Factor analysis was conducted on the data obtained through organizational commitment scale developed by Meyer and Allen (1990). Cronbach's alpha coefficient and also test item total correlation were calculated for reliability of the factors. Results confirmed the hypothesized relationship between job satisfaction and organizational commitment among employees of Tabung Haji Kedah.